Transendothelial migration of human umbilical mesenchymal stem cells across uterine endothelial monolayers: junctional dynamics and putative mechanisms - Ebrahim, Neven A.; Leach, Lopa (Elsevier, 2016)
Introduction: During pregnancy, fetal stem cells can transfer to the maternal circulation and participate in tissue repair. How they transmigrate across maternal endothelial barriers and whether they can subsequently influence maternal endothelial integrity is not known.